Employee Engagement Sebagai Variabel Mediasi Pengaruh Organizational Citizenship Behavior Terhadap Commitment Organizational - Prof. Dr. Yupono Bagyo, MM, MS, CHRP, CPTM; Yuli Siswidyastutik (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2021)
This study aims to determine whether there is an effect of OCB on Employee Engagement, OCB on Organizational Commitment, Employee Engagement on Organizational Commitment, and whether there is evidence that Employee Engagement as mediation effects Organizational Citizenship Behavior on Organizational Commitment. With the help of literature, the current study develops four hypotheses regarding Organizational Citizenship Behavior, Employee Engagement, and Organizational Commitment. The distribution of questionnaires was used for data collection at the Pasuruan City Financial and Asset Management Agency and the Pasuruan City Regional Revenue Agency with 59 employees and a sample of 50 employees. Using Partial Least Square as a data analysis method, the results show that OCB has a significant effect on Employee Engagement, OCB has a significant effect on Organizational Commitment, Employee Engagement has a significant effect on Organizational Commitment and OCB indirectly through Employee Engagement as an intervening variable has no significant effect on Commitment. Organizational